2013
DOI: 10.1073/pnas.1307879110
|View full text |Cite
|
Sign up to set email alerts
|

Isotropic band gaps and freeform waveguides observed in hyperuniform disordered photonic solids

Abstract: Recently, disordered photonic media and random textured surfaces have attracted increasing attention as strong light diffusers with broadband and wide-angle properties. We report the experimental realization of an isotropic complete photonic band gap (PBG) in a 2D disordered dielectric structure. This structure is designed by a constrained optimization method, which combines advantages of both isotropy due to disorder and controlled scattering properties due to low-density fluctuations (hyperuniformity) and un… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
204
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 212 publications
(210 citation statements)
references
References 37 publications
0
204
0
Order By: Relevance
“…The geometrical properties of hyperuniform point patterns have been extensively studied, in particular in terms of packing properties [21][22][23][24][25]. Regarding wave propagation, it has been shown that bandgaps could be observed for electromagnetic waves in two-dimensional (2D) disordered hyperuniform materials [26][27][28][29][30]. Although understanding the origin of the bandgaps is still a matter of study [31,32], these results have stimulated the design and fabrication of threedimensional (3D) hyperuniform structures for wave control at optical frequencies [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…The geometrical properties of hyperuniform point patterns have been extensively studied, in particular in terms of packing properties [21][22][23][24][25]. Regarding wave propagation, it has been shown that bandgaps could be observed for electromagnetic waves in two-dimensional (2D) disordered hyperuniform materials [26][27][28][29][30]. Although understanding the origin of the bandgaps is still a matter of study [31,32], these results have stimulated the design and fabrication of threedimensional (3D) hyperuniform structures for wave control at optical frequencies [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…We demonstrate that quality factors Q > 10 9 can be achieved for purely two-dimensional structures, and that for three-dimensional finite-height photonic slabs, quality factors Q > 20 000 can be maintained. A special class of disordered photonic heterostructures has recently been shown to display large isotropic band gaps comparable in width to band gaps found in photonic crystals [1][2][3]. The large band gaps found in these structures are facilitated by the hyperuniform geometrical properties of the underlying point-pattern template upon which the structures are built.…”
mentioning
confidence: 99%
“…A point pattern in real space is hyperuniform if for large R the number variance σ (R) 2 within a spherical sampling window of radius R (in d dimensions) grows more slowly than the window volume, i.e., more slowly than R d . In Fourier space, hyperuniformity means that the structure factor S(k) approaches zero as |k| → 0 [5,6].…”
mentioning
confidence: 99%
“…The second is by direct integration using Eqs. (12)(13)(14)(15). Note that the effect of pixelated space (i.e.…”
Section: Rectangular Particlesmentioning
confidence: 99%
“…Examples include jamming in amorphous materials [4,5,[7][8][9][10], complete optical band gaps in disordered photonics materials [11][12][13][14][15], and reversibility/irreversibility in periodically driven systems [16][17][18]. Hyperunformity is also important in the arrangement of photoreceptors in the retina [19], and in the large-scale structure of the universe [2].…”
mentioning
confidence: 99%